2005
DOI: 10.1128/jvi.79.14.9062-9068.2005
|View full text |Cite
|
Sign up to set email alerts
|

Novel Human Monoclonal Antibody Combination Effectively Neutralizing Natural Rabies Virus Variants and Individual In Vitro Escape Mutants

Abstract: The need to replace rabies immune globulin (RIG) as an essential component of rabies postexposure prophylaxis is widely acknowledged. We set out to discover a unique combination of human monoclonal antibodies (MAbs) able to replace RIG. Stringent criteria concerning neutralizing potency, affinity, breadth of neutralization, and coverage of natural rabies virus (RV) isolates and in vitro escape mutants were set for each individual antibody, and the complementarities of the two MAbs were defined at the onset. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
120
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 138 publications
(126 citation statements)
references
References 25 publications
2
120
0
3
Order By: Relevance
“…This would indicate that the epitope(s) on the virions associated with the neutralizing activity of Fab is probably not directly correlated to their binding specificity for JEV antigens detected by ELISA, which is supported by previous reports (4,12). Purified Fab molecule was prepared from TJE12B02 which showed the highest JEV strain Nakayama neutralizing activity, and the highest standardized value for antigen-binding activity to the same strain (Table 1).…”
Section: Discussionsupporting
confidence: 74%
“…This would indicate that the epitope(s) on the virions associated with the neutralizing activity of Fab is probably not directly correlated to their binding specificity for JEV antigens detected by ELISA, which is supported by previous reports (4,12). Purified Fab molecule was prepared from TJE12B02 which showed the highest JEV strain Nakayama neutralizing activity, and the highest standardized value for antigen-binding activity to the same strain (Table 1).…”
Section: Discussionsupporting
confidence: 74%
“…As recent studies suggested that resistance to monotherapy with MAb E16 can occur in vivo (84), the use of combinations of neutralizing MAbs that recognize distinct epitopes may be advantageous, as was demonstrated previously for a therapeutic antibody cocktail against rabies virus (2). The characterization of potently neutralizing MAbs like CR4348 and CR4354 that map to distinct regions and inhibit virus by different mechanisms suggests that this may be feasible.…”
Section: Discussionmentioning
confidence: 99%
“…B, schematic diagram of expanded view of the ␤-sheet formed by the three strands, which could disrupt by deleting C-terminal residues. C, surface plot of SEB shows mutated residues (red color) which are distinct from D the MHC surface (rotating 180 degrees around vertical axis) shows in cyan (residues 43, 44, 45, 46, 47, treatment of viral diseases including rabies and SARS, combination of mAbs against wild-type epitope and variant epitope can prevent the emergence of escape variants (47,48). Moreover several studies have shown that targeting more than one adhesion protein with mAb in S. aureus infection can be beneficial (49,50).…”
Section: Discussionmentioning
confidence: 99%